Subjects of defence procurement: legal status and interaction specifics - Matvieiev, O. M. (Аналітично-порівняльне правознавство, 2025)
The article presents a comprehensive analysis of the legal status of defence procurement entities in Ukraine. Based on a systematic examination of the regulatory framework and academic sources, the study identifies the legal features of the main categories of actors involved and the specifics of their interaction within the defence procurement system. It is substantiated that, unlike conventional public procurement, where participation is primarily determined by economic parameters, the sphere of defence procurement is governed by additional criteria such as strategic significance, security considerations, and state secrecy regulations. The author establishes that the legal status of defence procurement entities is formed at the intersection of several legal regimes: administrative regulation of public procurement, national security legislation, and specific provisions of defence law. This results in a complex legal institution that combines the general principles of public procurement with the specific requirements of the defence sector. The legal status of the Cabinet of Ministers of Ukraine as the coordinating authority within the defence procurement system is explored, with three distinct groups of powers identified and characterised. The legal position of the key body responsible for defence procurement planning—the Ministry for Strategic Industries – is analysed. The article also outlines the multifaceted legal status of the Ministry of Defence of Ukraine as the principal body responsible for executing defence procurement. Its powers encompass registration and accounting, economic and analytical functions, regulatory and coordination responsibilities, anti- corruption efforts, and strategic planning. The legal status of state customers in the defence procurement system is defined, with key functional dimensions identified: planning and administrative-budgetary, economic-financial, technical-design, quality-control, and coordination and interaction. The legal status of state contract executors is also examined, highlighting their commercial autonomy alongside heightened requirements for the quality, reliability, and safety of defence products.